Design and Development of a Serious Game for the Teaching of Requirements Elicitation and Analysis - Ibrahim Z.; Soo M.C.; Soo M.T.; Aris H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Education computing; Engineering education; Requirements engineering; Software design; Students; Computer science students; Design and Development; Development phase; Learning objectives; Overall design; Requirements elicitation; Students' interests; Younger generations; Serious games